Alveolar rhabdomyosarcoma metastatic to the brain - Rodriguez-Beato, Freddie (BMJ Case Rep, 2021)
Alveolar rhabdomyosarcoma (ARMS) has a predilection for the peripheral extremities, and brain metastases are rare, with only a few cases reported after the initial diagnosis. We present a 22-year-old male patient with a right orbital-ethmoidal ARMS who presented with a recurrence to the brain 1 year after the initial diagnosis. He was referred to our institution due to acute neurological deterioration. A brain MRI was performed, showing an enhancing bilateral parafalcine lesion centred about the bilateral cingulate gyri with extension into the corpus callosum. The patient was taken to the operating room for a stereotactic biopsy under general anaesthesia, which was compatible with metastatic ARMS. Our case is exceedingly rare, considering the initial diagnosis of an orbital/ethmoidal ARMS, its subsequent metastasis to the brain and its clinical sequelae after a biopsy. Prognosis after cerebral metastatic ARMS is dismal, with most patients expiring due to central nervous system metastatic disease.